Pengaruh Belanja Hibah, Belanja Bantuan Sosial, Belanja Bantuan Keuangan, dan Belanja Fasilitas Umum Terhadap Keterpilihan Petahana dalam Pemilukada 2017 - Ummu Auliyah; Suhairi Suhairi; Nini Syofri Yeni (Universitas Batanghari Jambi, 2020)
This study aims to determine the effect of grant expenditure, social assistance expenditure, financial aid expenditure and public facility expenditure on incumbent election in the General Election of Regional Head conducted in 2017. The type of this research is quantitative descriptive research. The objects examined are grant expenditure, social assistance expenditure, financial aid expenditure, and public facility expenditure in the 2015-2016 regional budget. The year 2015 represented shopping data prior to the General Election of Regional Head, while 2016 represented spending data at the time of the General Election of Regional Head. This study uses a logistic regression statistical test. The data analysis tool used for hypothesis testing is the Wald test. The results of this study state that there is no relationship between the independent variable and the dependent variable, but almost all regions have an increase in grant expenditure, financial aid expenditure, and public facilities ahead of the implementation of the General Election, while the average social assistance expenditure has decreased.